Whole-Genome Sequencing in Newborn Screening-Attitudes and Opinions of Bulgarian Pediatricians and Geneticists - Georgi Iskrov; Georgi Iskrov; Stefan Ivanov; Stephen Wrenn; Rumen Stefanov; Rumen Stefanov (Frontiers Media S.A., 2017)
ObjectiveThe aim of this study was to assess the attitudes and opinions on the potential use of whole-genome sequencing (WGS) in conjunction with the traditional newborn screening (NBS). We conducted an online survey among pediatricians and geneticists from Bulgaria. The study was based on the concept of non-selective WGS for all newborns and analysis of all genes.Results/conclusionIn total, 120 out of 299 invited participants completed the survey, with an overall response rate of 40.1%. While half of the pediatricians surveyed supported population-based non-selective WGS in NBS, 65.2% of the geneticists expressed concerns. Most participants underlined that ethical issues were as important as medical ones and called for a stricter protection of affected individuals against any abuse of their personal data. Extensive genetic counseling and psychological support to families were mentioned as key elements in this potential activity. Nevertheless, both pediatricians and geneticists considered that NBS in Bulgaria could be further developed, with selective WGS being suggested as a potential option. While non-selective WGS for all newborns is not currently perceived as feasible, pediatricians and geneticists do believe that selective WGS could strengthen current NBS programs. Cross-border project collaborations may set the stage for generating experience and evidence on these complex issues.